2008
DOI: 10.1248/jhs.54.162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxyhydroquinone-reduced Coffee on Blood Pressure in High-normotensives and Mild Hypertensives

Abstract: The influence of hydroxyhydroquinone (HHQ) on the antihypertensive effects of chlorogenic acids in coffee was evaluated in a double-blind, randomized controlled trial of high-normotensive and mild hypertensive adult men and women. The subjects were randomly assigned to either an active group that ingested HHQ-reduced coffee (0.05 mg/184 ml) containing chlorogenic acids (299 mg/184 ml) or a control group that ingested coffee containing HHQ (1.69 mg/184 ml) and chlorogenic acids (299 mg/184 ml), corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…In our study, coffee consumption led to a significant decrease of systolic blood pressure in the D-group, but final values reached were not significantly different from the group consuming M-coffee. Dark roast coffee has been reported previously to increase rather than reduce blood pressure, which is thought to result from a lower content of CQA and a higher content of hydroxyhydroquinone, when compared to mildly roasted or green coffee [14,42,43]. The reason for the difference in outcome is not known, since NMP concentration had not been measured in above studies, and the content of hydroxyhydroquinone was not determined in the coffee preparations used in our study.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, coffee consumption led to a significant decrease of systolic blood pressure in the D-group, but final values reached were not significantly different from the group consuming M-coffee. Dark roast coffee has been reported previously to increase rather than reduce blood pressure, which is thought to result from a lower content of CQA and a higher content of hydroxyhydroquinone, when compared to mildly roasted or green coffee [14,42,43]. The reason for the difference in outcome is not known, since NMP concentration had not been measured in above studies, and the content of hydroxyhydroquinone was not determined in the coffee preparations used in our study.…”
Section: Discussionmentioning
confidence: 64%
“…The studies were conducted in different countries (20,22,28), with the 3 most recent studies carried out in Japan (23)(24)(25). All included persons of both sexes were aged !20 y.…”
Section: Tablementioning
confidence: 99%
“…Loss to follow-up was ,10% in all studies, and in the study of Rakic et al (22) there were no losses. The BP values were based on the mean of 24-h ambulatory blood pressure monitoring in 3 studies (20,22,28), and on !2 BP readings in the remaining studies (23)(24)(25). The cutoff points to define hypertension were heterogeneous, and the oldest study (20) considered only the DBP value.…”
Section: Tablementioning
confidence: 99%
“…The HHQ-reduced and control beverages contained (per 184 ml) 299 mg chlorogenic acids and, 0.05 and 1.69 mg HHQ, 77 and 75 mg caffeine, and 29.3 and 37.7 kJ, respectively. 23) The Study Protocol --The study design was a randomized, double-blind, crossover controlled trial (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Chikama et al reported that 12 weeks of continuous ingestion of the chlorogenic acids contained in HHQ-reduced coffee decreased blood pressure and improved vascular endothelial function in untreated mildly hypertensive subjects. [20][21][22][23] Based on these findings, HHQ-reduced coffee might have great public health benefits.…”
Section: Introductionmentioning
confidence: 99%